2014
DOI: 10.1016/j.ajog.2014.02.033
|View full text |Cite
|
Sign up to set email alerts
|

First-trimester placental ultrasound and maternal serum markers as predictors of small-for-gestational-age infants

Abstract: Objective To combine early, direct assessment of the placenta with indirect markers of placental development to identify pregnancies at greatest risk of delivering small-for-gestational age infants (SGA10). Methods We prospectively collected 3D-ultrasound volume sets, uterine artery pulsatility index (UtAPI) and maternal serum of singleton pregnancies at 11–14 weeks. Placental volume (PV), quotient (PQ=PV/gestational age), mean placental and chorionic diameters (MPD and MCD, respectively), and the placental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 49 publications
5
78
2
Order By: Relevance
“…The explanation might be that SGA infants in our study represented a very mild form of SGA having mean delivering time at term and mean birth weight only slightly below 10 th percentile. Concentrations of PlGF in normotensive women with SGA infants have been shown to be lower already in the first trimester as compared to controls [50], but in other studies differences in PlGF concentrations have only been present in the second trimester [51] or not at all [52]. …”
Section: Discussionmentioning
confidence: 99%
“…The explanation might be that SGA infants in our study represented a very mild form of SGA having mean delivering time at term and mean birth weight only slightly below 10 th percentile. Concentrations of PlGF in normotensive women with SGA infants have been shown to be lower already in the first trimester as compared to controls [50], but in other studies differences in PlGF concentrations have only been present in the second trimester [51] or not at all [52]. …”
Section: Discussionmentioning
confidence: 99%
“…This same team even set up specific risk algorithms for screening SGA neonates and preeclampsia by a combination of maternal characteristics and history with biochemical (PAPP-A, PLGF) and biophysical markers (uterine artery pulsatility index, MAP) [22,23]. Similarly, the study conducted by Schwartz et al [24] built a multivariable model of combining indirect markers of placental development (PLGF and placental protein 13) and direct assessment of the placenta at around 11-14 weeks of gestation for the early prediction of SGA. The changes of these biophysical and biochemical markers are thought to be related to placental insufficiency and were gradually utilized widely as predictive tools for SGA pregnancies and preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…This model uses the linear measurements of placental width, height and thickness to calculate the volume of an elliptical cylinder and has been correlated to placental weights (18). EPV measurements by 2D and 3D ultrasound have been used in several studies across all gestations and have been found to correlate significantly with gestational weight at delivery (1921). …”
Section: Methodsmentioning
confidence: 99%
“…A power calculation was performed and we were adequately powered (power > 90%) to detect a mean difference in EPV of anywhere between 1 and 15 cm 3 with our sample size. We selected the EPV between 1 and 15 cm 3 since fetal growth restriction has been associated with fertility treatments and an EPV of 15 cm 3 is a predictor of fetal growth restriction based on a study by Schwartz, et al (19)…”
Section: Methodsmentioning
confidence: 99%